2016
DOI: 10.1097/qad.0000000000001111
|View full text |Cite
|
Sign up to set email alerts
|

Option A improved HIV-free infant survival and mother to child HIV transmission at 9–18 months in Zimbabwe

Abstract: Objective We evaluated the impact of Option A on HIV-free infant survival and mother-to-child transmission (MTCT) in Zimbabwe. Design Serial cross-sectional community-based serosurveys. Methods We analyzed serosurvey data collected in 2012 and 2014 among mother-infant pairs from catchment areas (CAs) of 132 health facilities from 5 of 10 provinces in Zimbabwe. Eligible infants (alive or deceased) were born 9–18 months before each survey to mothers ≥16 years old. We randomly selected mother-infant pairs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…Compared to three studies of population-level MTCT rates, the 2016 modelled estimates are within the confidence intervals, or comparable, to the study results[2123]. The modelled transmission rates for South Africa at age six weeks in the calendar year 2011 was 4.0% while the transmission rate from the South African Impact Assessment was 3.5% (2.9%–4.1%)[22] (see Figure 4).…”
Section: Resultssupporting
confidence: 64%
“…Compared to three studies of population-level MTCT rates, the 2016 modelled estimates are within the confidence intervals, or comparable, to the study results[2123]. The modelled transmission rates for South Africa at age six weeks in the calendar year 2011 was 4.0% while the transmission rate from the South African Impact Assessment was 3.5% (2.9%–4.1%)[22] (see Figure 4).…”
Section: Resultssupporting
confidence: 64%
“…Mother-to-child-transmission risk Compared to two studies of population-level MTCT rates, the 2016 modelled estimates are within the confidence intervals (CIs), or comparable, to the study results [22,23]. The modelled transmission rates for South Africa at age 6 weeks in the calendar year 2011 was 4.0%, whereas the transmission rate from the South African Impact Assessment was 3.5% (2.9-4.1%) [22] (see Fig.…”
Section: Validation Of Spectrum Projectionssupporting
confidence: 55%
“…[7] In a community-based survey in Zimbabwe in 2014 (post-Option A rollout), HIV-free survival was reported as 95.1%. [11] In South Africa, results in a prospective facility-based cohort study showed an HIV-free survival rate of 93.7% at 18 months[12], while in Nigeria, HIV-free survival was reported to be 86.2% at 18 months in a facility-based retrospective cohort study. [13]…”
Section: Discussionmentioning
confidence: 99%
“…[7] In Zimbabwe, MTCT of HIV was estimated at 4.8% in the post-Option A implementation period. [11] Using Spectrum models, MTCT in 2015 in Swaziland is estimated at 6.72% by the end of breastfeeding. [18] The difference between our findings and the Spectrum estimates may be due to differences in methodology (i.e., use of models vs observational study) and the possibility that our study had inaccurate ascertainment of child death, as discussed earlier.…”
Section: Discussionmentioning
confidence: 99%